Predictive Analysis Of Ice, Hybrid And Electric Vehicle: Selected Case Studies - Mohd Shafee, Muhammad Amirul Farhan (Universiti Sains Malaysia, 2022)
Global warming is one of the most spoken issues around the world today. This is because the global warming has a significant impact on the human and environment. One of the biggest factors that causes global warming is the transportation sector. Internal combustion engine vehicle that runs on gasoline emits carbon dioxide, hence contributing to the greenhouse gas emission. Therefore, a counter measure needs to be taken to lessen the impact of internal combustion engine through the use of hybrid and electric powertrain. In this study, the carbon footprint for ICEV, PHEV and BEV will be determined through the life-cycle analysis. The models that will be used in this selected case study is BMW 3-Series as it has a wide range of powertrain from ICE to electric. Since all of the vehicles has the same size, same design and manufactured by the same company in the same factory, therefore the difference between each vehicle is negligible. Next, the forecasting of car sales trend for each powertrain can be made through the simulation in MATLAB Simulink. By correlating both of the data for carbon emission and car sales data, the forecasting of carbon footprint for each powertrain in the future can be made. Among 3 scenarios that is made, it is found out that scenario 1 emits the highest CO2 emission at 1.80688 X 10^12 kgCO2, followed by scenario 3 at 1.58632 X 10^12 kgCO2 and the least contributor for CO2 emission is scenario 2 at 4.6252 X 10^11 kgCO2.